Serpula similis (Berk and Broome) Ginns, A Fungal Pathogen Causing Rhizome Decay and Root Rot in Thyrsostachys voliveri Bamboo Exhibiting Phenomenon of Guttation in Natural Condition-A New Record - Singh, A. N. (Indian Forester, 2020)
No Abstract.